ANALISIS KOMPARASI KINERJA KEUANGAN PERUSAHAAN INDUSTRI DASAR DAN KIMIA DI BURSA EFEK INDONESIA SEBELUM DAN SELAMA PANDEMI COVID-19 - Yuswinta Adjeng Pratiwi; Dwi Tirta Kencana (Journals of Economics and Business, 2022)
AbstractThis study aims to analyze the comparison of the impact of the COVID-19 pandemic on the financial performance of companies in the Basic and Chemical Industry Sector listed on the Indonesia Stock Exchange. The population in this study includes all companies in the Basic and Chemical Industry Sector listed on the Indonesia Stock Exchange. The sample was determined by purposive sampling technique and acruired 34 companies. The research period used was quarters 2, 3, and 4 of 2019 and quarters 2, 3, and 4 of 2020. The total numbers of samples is 102 samples. This research in a type of comparative quantitative research. Data analysis methods used in this study includes descriptive statistics, normality tests, and hypothesis tests used wilcoxon signed rank test because the data is not normally distributed. The test result showed that wilcoxon signed rank test for NPM, ROA, EPS and TATO ratios before and during COVID-19 had an Asymp. Sig (2-tailed) is less than the significance value α= 0,05 (0,05). It means that there were significant differences in NPM, ROA, EPS and TATO before and during COVID-19. As for ROE, CR, DER and PER before and during COVID-18 had an Asymp. Sig (2-tailed) is greater than significance value α= 0,05 (0,05). This means that there’s no difference in the ROE, CR, DER and PER.Keywords: Financial Performance, Financial Ratio, Before and During COVID-19